A Rare Primary Neuroendocrine Tumor (Typical Carcinoid) of the Sublingual Gland. (20th October 2016) - Yamagata, Kenji; Ohki, Kousuke; Uchida, Fumihiko; Kanno, Naomi; Hasegawa, Shogo; Yanagawa, Toru; Bukawa, Hiroki
Abstract : A typical carcinoid is extremely rare in the oral cavity. We here present a case of a typical carcinoid arising in the sublingual gland of a 62-year-old woman. The tumor was removed by primary excision with 10 mm surgical margins and submandibular dissection. Examination of the tumor showed medium-sized tumor cells that were positive for CD56 and chromogranin A, with no necrosis, and with a mitotic count less than 1/10 HPF. A pathological diagnosis of typical carcinoid was made from both morphological and immunological examinations. One year after excision surgery, there was no tumor recurrence or neck metastasis.